Nursing perspectives on care delivery during the early stages of the covid-19 pandemic: A qualitative study (2020)
Background: Research examining RNs’ experiences during the COVID-19 pandemic is lacking, thus inhibiting efforts to optimize nursing care delivery and patient outcomes during the current pandemic and future public health emergencies. Objective: To explore the experience of being a registered nurse caring for patients with COVID-19 at an urban academic medical center during the early stages of the pandemic Design: Qualitative descriptive study, guided by Donabedian’s Quality Framework for Evaluation of Healthcare Delivery which focuses on structures, processes, and outcomes of care delivery Setting: Urban academic medical center in the northeast United States Participants: Registered nurses cared for or caring for patients with COVID-19, age ≥18 years old, and English-speaking Methods: Participants were recruited for individual in-person semi-structured interviews. Interviews occurred during March and April 2020 and were recorded and transcribed. Transcripts were analyzed by two researchers using emergent qualitative content analysis to identify themes. Results: Twenty-one registered nurses participated in the study. Three themes emerged from the data, included one relevant to structures and two relevant to processes of care during the pandemic. Registered nurses perceived the clinical context as highly dynamic, but quickly adapted to pandemic-related care delivery. They felt a “sense of duty” to care for patients with COVID19, despite being fearful of acquiring or spreading infection. Compared to clinical colleagues, registered nurses reported increased patient exposure and performed tasks previously assigned to other clinical team members. Conclusion: Roles and nursing practice processes evolved to meet the demand for care despite challenges. Registered nurses require adequate protection for their frontline role which may consist of increased patient exposure compared to clinical colleagues, emotional support, and clear clinical guidance. A deeper understanding of how a public health emergency, such as the COVID19 pandemic, affects nursing practice can guide future efforts to optimize healthcare structures, nursing care processes, and patient outcomes. Our study can inform strategies for providing registered nurses with adequate communication, protection, and resources during the COVID-19 pandemic and future similar public health emergencies.